Gestão e desenvolvimento de política social pública para idosos : uma análise fundamentada no princípio da eficiência - Oliveira, Soraya Francisca Dinkhuysen (2014)
This research aims to analyze the public management of social actors in programs and projects for the elderly in the city of PassoFundo, with a view to obtaining grants for your full attention. Will take into account the priorities of public policies for social care in elderly care from the perspective of management programs that work on issues of human aging in Passo Fundo. They will also analyze programs and projects of care for the elderly, developed and deployed by public management between 2009 and 2012, discussed in the light of the principle of efficiency. When a child is born, it is customary to give attention to your future, in terms of health, education, profession, friendship, marriage, family. However, little is discussed about how we prepare for old age, even healthy and successful. The maturation process and their understanding of this subject - the elder - will be analyzed in this research, especially in recent decades in Brazil, being the social aging factor constituted and constructed by cultural dimension of society. The objectives of the study allow a review about the process used in the construction of public social policies and also a knowledge of the relationship between the role of management and the role of social actors in the construction of social policies for the elderly in the light of the principle of efficiency. The limitations of this research are concentrated on the holding of a specific reality, and may be its merits, because the results of such a study can be translated into subsidies for other situations exercising public social management in the implementation of programs and projects. In this alignment, information and knowledge in question in the field of gerontology, specifically in the laws pertaining to managers, are of vital importance to direct budgetary implementation in the fulfillment of social rights for the elderly and for building effective public policies in developing laws for basic social protection